Growth of wafer-scale MoS2 monolayer by magnetron sputtering1. Issue 6 (14th February 2015) - Tao, Junguang; Chai, Jianwei; Lu, Xin; Wong, Lai Mun; Wong, Ten It; Pan, Jisheng; Xiong, Qihua; Chi, Dongzhi; Wang, Shijie
<x xml:space="preserve">Abstract</x> The two-dimensional layer of molybdenum disulfide (MoS2) exhibits promising prospects in the applications of optoelectronics and valleytronics.